Report on the Phytoplankton Pigments measured during the JARE-35 Cruise to Syowa Station, Antarctica, November 1993 to March 1994 - Kawachi, Masanobu; Suzuki, Toshikazu; Fukuchi, Mitsuo (National Institute of Polar Research, 1996)
P(論文) departmental bulletin paper